2019
DOI: 10.1177/0886260518822341
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity, Injury, and Death: Implications for Anti-Knife-Carrying Messages

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In sum, the research on fear-based media campaigns is mixed (Tannenbaum et al, 2015). Palasinski et al (2021) found that injury-related messaging was persuasive in a sample of young adult males, but their study measured tolerance towards knife-carrying (e.g. whether it could be seen as acceptable and justified), rather than intentions or behaviours surrounding knife crime.…”
Section: Fear Appeals In Anti-knife Carrying Media Campaignsmentioning
confidence: 99%
See 3 more Smart Citations
“…In sum, the research on fear-based media campaigns is mixed (Tannenbaum et al, 2015). Palasinski et al (2021) found that injury-related messaging was persuasive in a sample of young adult males, but their study measured tolerance towards knife-carrying (e.g. whether it could be seen as acceptable and justified), rather than intentions or behaviours surrounding knife crime.…”
Section: Fear Appeals In Anti-knife Carrying Media Campaignsmentioning
confidence: 99%
“…By contrast, Palasinki et al (2021) recently conducted a series of studies exploring the effect of exposure to different anti-knife carrying slogans and posters on knife-carrying tolerance among adult males aged 18–25 years. They found that injury-related slogans and posters – those emphasising physical trauma – were the most persuasive types of messaging, compared to those emphasising pathology (i.e.…”
Section: Fear Appeals In Anti-knife Carrying Media Campaignsmentioning
confidence: 99%
See 2 more Smart Citations
“…They questioned nearly 600 young men about the messages depicted by anti-knife posters and slogans. This is relevant to England and Jackson’s program, because Palasinski et al (2019) found that the most effective slogans and posters were those that focused on the potential injury of knife carrying. Anecdotally, young men specifically mentioned that posters depicting eye injury were the most persuasive.…”
Section: International Literature On Knife Violencementioning
confidence: 99%